2000
DOI: 10.1016/s0272-7757(99)00035-7
|View full text |Cite
|
Sign up to set email alerts
|

Spending, school structure, and public education quality. Evidence from California

Abstract: This paper examines school structure, spending, and performance relationships in California and finds considerable support for the public exchange model that predicts that greater competition improves student performance. The evi dence indicates that, despite claims to the contrary by many advocates of public education, higher education spending does not raise student achievement. Education spending is also shown to be highest in those counties exhibiting highest monopoly power as measured by the Herfindahl in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 39 publications
1
22
0
10
Order By: Relevance
“…Specifically, he employed the seemingly unrelated regression model and estimated the effects of competition on students' academic achievement controlling for a series of educational inputs (spending, teacher/student ration etc.). The result showed that 10 out of 18 estimations were not statistically significant (Marlow, 2002). Moreover, when the estimates were significant, they were not consistent across the grades.…”
Section: School Choice and Competitionmentioning
confidence: 82%
See 2 more Smart Citations
“…Specifically, he employed the seemingly unrelated regression model and estimated the effects of competition on students' academic achievement controlling for a series of educational inputs (spending, teacher/student ration etc.). The result showed that 10 out of 18 estimations were not statistically significant (Marlow, 2002). Moreover, when the estimates were significant, they were not consistent across the grades.…”
Section: School Choice and Competitionmentioning
confidence: 82%
“…Employing the Herfindahl Index and Grade Level Performance Assessments dataset Marlow (2002) examined the effects of competition on students' academic performance in California. Although he concluded that greater competition improves student performance, the result of the study is somewhat mixed.…”
Section: School Choice and Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some studies, however, that have produced more mixed findings (Borland & Howson, 1992, 1996Marlow, 1999), but none of these findings was distinctly negative for the use of Tiebout choice.…”
Section: Previous Research and Theoretical Expectations On The Effectmentioning
confidence: 97%
“…Mais recentemente, esse autor, em parceria com outros estudiosos, concluiu que os recursos destinados às escolas nos Estados Unidos têm sido gastos de maneira improdutiva e não têm contribuído para um melhor desempenho dos discentes, dando importância, portanto, ao emprego dos recursos muito mais do que ao montante despendido (Hanushek, 1994, apud Lavy, 1998Hanushek, Rivkin, Taylor, 1996). Conclusão semelhante teve Marlow (2000), para quem o problema da baixa qualidade das escolas públicas americanas é a estrutura de monopólio do sistema educacional, e não a carência de recursos.…”
Section: As Conclusões Da Corrente Majoritáriaunclassified